Soil insect research in South Africa. 1. A new genus of terricolous weevils with four new species from the Richtersveld National Park (Coleoptera: Curculionidae: Entiminae: Trachyphloeini) - Borovec, R.; Meregalli, M. (Zootaxa, 2013)
The new genus, Nama gen. n., and four new species, N. richtersveldiana sp. n., N. pentamera sp. n., N. iuliae sp. n. and N. erikae sp. n., are described from the Richtersveld National Park. The taxonomic position of the new genus is discussed, and it is compared with the other Trachyphloeini native to South Africa and with some genera of Trachy-phloeini occurring in the Palaearctic region. A key to the species of Nama is provided.